Basalt Fibre Reinforcement of Bent Heterogeneous Glued Laminated Beams - Wdowiak-Postulak, Agnieszka (Materials (Basel), 2020)
The purpose of this paper is to demonstrate the properties of glued laminated beams made in diverse configurations of timber quality classes, reinforced using a new technique that is cheaper and easy to apply. The aim of the experimental investigations was to enhance reinforcement effectiveness and rigidity of glued laminated beams. The tests consisted of four-point bending of large-scale specimens reinforced with basalt fibres (BFRP). The tests were meant to obtain images of failure, the load–displacement relation and load carrying capacity of basalt fibres depending on the reinforcement ratio. The tests, which concerned low and average quality timber beams, were conducted in a few stages. The aim of the study was to popularize and increase the use of low-quality timber harvested from reafforested areas for structural applications. In the study, theoretical and numerical analysis was carried out for reinforced and unreinforced elements in various configurations of wood quality classes. The aim was to compare the results with the findings of experimental tests. Based on the tests, it was found that the load carrying capacity of beams reinforced with basalt fibre was higher by, respectively, 13% and 20% than that of reference beams, while their rigidity improved by, respectively, 9.99% and 17.13%. The experimental tests confirmed that basalt fibres are an effective structural reinforcement of structural timber with reduced mechanical properties.